2002
DOI: 10.1186/1471-244x-2-10
|View full text |Cite
|
Sign up to set email alerts
|

Mental health first aid training for the public: evaluation of effects on knowledge, attitudes and helping behavior

Abstract: Background: Many members of the public have poor mental health literacy. A Mental Health First Aid training course was developed in order to improve this. This paper describes the training course and reports an evaluation study looking at changes in knowledge, stigmatizing attitudes and help provided to others.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
332
2
13

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 353 publications
(358 citation statements)
references
References 10 publications
11
332
2
13
Order By: Relevance
“…These findings are congruent with those published by the developers of the MHFA training program (Kitchener & Jorm, 2002;Kitchener & Jorm, 2006;Jorm et al, 2007), who asserted that those who did the training showed a number of changes such as improvement in recognising mental illness and being more like health professionals in their beliefs about what treatments are likely to be helpful.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These findings are congruent with those published by the developers of the MHFA training program (Kitchener & Jorm, 2002;Kitchener & Jorm, 2006;Jorm et al, 2007), who asserted that those who did the training showed a number of changes such as improvement in recognising mental illness and being more like health professionals in their beliefs about what treatments are likely to be helpful.…”
Section: Discussionsupporting
confidence: 81%
“…Training of the non-health sector has been shown to be a valuable approach in supporting people with mental health problems (Kitchener & Jorm, 2002). During focus groups run by the authors, the need for this training was identified by the employers of Farm Advisors who recognised that those advisors are often the first access point to farmers with mental health problems.…”
Section: Discussionmentioning
confidence: 99%
“…Certain versions of MHFA are less reductive than others, however, MHFA never strays from its psychiatric disciplinary underpinnings (Kitchener & Jorm, 2002). According to Hart, Jorm, Kanowski, Kelly, and Langlands, (2009, para.…”
Section: Reductionismmentioning
confidence: 99%
“…More than one decade of evaluative scholarly literature acknowledges the international Mental Health First Aid (MHFA) movement as an extraordinary humanitarian success (Hadiaczky, Hokby, Mkrtchian, Carli, & Wasserman, 2015;Kitchener & Jorm, 2002). MHFA training seminars, central to this global movement, prepare lay citizens to provide immediate MHFA to persons perceived as distressed and presumed to be experiencing "a mental health problem" (Kitchener & Jorm, 2008).…”
mentioning
confidence: 99%
“…It will also require people to be aware of what to do in the case of identifying early signs of mental illness in themselves or in someone they know. Mental health First Aid (Kitchener & Jorm, 2002) is an ideal method for achieving these aims. Another key reform will be extending the period of time in which someone will be able to be treated.…”
Section: To Finally Close the Gap Between What Can Be Done And What Imentioning
confidence: 99%